Membangun Semangat Pendidikan dengan Puasa - Muhirdan, Muhirdan (Al-Riwayah : Jurnal Kependidikan, 2018)
Ramadan fasting is a mandatory worship for the faithful both men and women as well as past and later ones. Fasting during Ramadan that Allah prescribes in the Qur'an has a certain meaning and purpose. This paper will explain the meaning of the word 'Ramadan' and the purpose of fasting, and the meanings associated with the words ‘knowledge’ (‘ilm) described in the verses of the Quran and the Hadis of the Prophet Muhammad. This paper also aims to know about the religiosity and degrees (maqamat) that can be gained by faithful associated with worship based on knowledge. In addition, in the conduct of worship, a person needs knowledge. People who are knowledgeable and faithful will be given a higher degree by God because the knowledgeable people will obey and submit to God. Thus, it can be concluded that faith, knowledge, and worship are triangles whose sides connect and fill one another and are inseparable. Acts of kindness, noble character (amal shalih) has done by the faithful and knowledgeable can lead him to achieve the predicate of takwa as the highest degree.